Temperature effect on the physical and electronic properties of Single Walled Carbon Nanotubes - Dereli, G.; Suengue, B.; Eyecioglu, Oe.; Vardar, N. (AMER INST PHYSICS, 2007)
The effects of slow temperature increase on the structural stability and the electronic properties of Single Walled Carbon Nanotubes (SWCNTs) are studied using the Order N, parallel Tight Binding Molecular Dynamics algorithms (TBMD) of [1-3]. Constant volume, constant temperature, canonical ensemble Molecular Dynamics algorithms are employed. Simulations are performed in the parallel environment of YTU Carbon Nanotube Simulation Laboratory [4]. Temperature is controlled by rescaling the velocities. Electronic temperature (k(B)T) is also taken into account. Using these algorithms SWCNTs are stable upto 2000K. As the temperature increases the band gap of the semiconducting SWCNTs gets narrower.
Keywords: Single Wall Carbon Nanotube; molecular dynamics; parallel; Order N algorithms; thermal; electronic; Physics